Students’ understanding, attitude and experience on dishonesty and plagiarism: How undergraduate and postgraduate students of English Education resemble and/or differ - Safnil Arsyad; Azwandi; Alamsyah Harahap (UNIB Press, 2023)
It is much easier to access literature now than before because of the existence of the internet where students can download soft files of articles or written works from journals or particular websites. However, postgraduate students especially those studying at a teacher education program should not plagiarize because they become role models for their students and should present noble behaviour for their students to be. This study investigated how much undergraduate and postgraduate students in English education are familiar with plagiarisms, how their attitudes toward plagiarism are and what may encourage them to plagiarize. The data for this study came from 151 students involved in this study by filling in the questionnaire and 6 of them were randomly selected for interview. The results show that in general there is no important difference between undergraduate and postgraduate students on their knowledge, attitude, and experiences of dishonesty and plagiarism although there are some differences in the percentage of the two groups of students on several items asked in the questionnaire. This implies that the level of education does not affect university students of their knowledge, attitude and experience on dishonesty and plagiarism. Therefore, it is recommended that specific training programs on academic writing which include moral ethic, knowledge on dishonesty and plagiarism and their practical samples in written texts to combat dishonesty and plagiarism among university students at any level.